Kondisi Pendidikan Pekerja Anak Usia Sekolah Di Tempat Pembuangan Akhir (TPA) Sampah - Lelya Hilda (IAIN Padangsidimpuan, 2018)
This research is based on the problems on low economy of the societies that make the children help their parents to have working to fulfill their needs. Meanwhile, children still need to play and to study, it is not their responsible to join to handle the needs of their economy. The purposes of this research are to know the condition of education of the children workers in TPA Batu Bola Padangsidimpuan. Beside, the researcher also wanted to know the factors caused them doing work in that place, and the parents and government effort to protect the children. The research is qualitative descriptive. The informant are children workers (pick workers/pemulung), their parents, as the primer source and other pick workers, and the district government (lurah) as the secondary source. The instruments used are questionnaires, interview, observation, adn documentation. Based on the research, it is found that the children are 12 persons from Junior High School (40%), 9 persons from Junior High School (30%), 2 persons from Senior High School (6.67%), and out of school 7 persons (23.33%). The main factors that make them work is because of the pressure of the economic needs. The reasons are asked by their parents (80%), their wants (13.33%), and asked by their friends (6.67%). The parents effort by giving advises to their children, and the government didnot have hard regulation and solution in order to make them always in that condition.